INNOVATIVE MARKETING COMPLEX: ITS COMPONENTS, METHODS AND TOOLS - Kalinichenko, Olena; Kaschuck, Kateryna (Zhytomyr Ivan Franko State University, 2020)
The article examines the state of innovation system in Ukraine. This state is defined as a crisis and such that it does not correspond to the current level in countries that have taken the path of innovative development. Low indicators were revealed that characterize innovative activity in industry, the state of which directly affects the rates of development in almost all sectors of the economy. It has been established that in order to develop an enterprise, increase its competitiveness and achieve leadership positions, it is necessary to observe two areas of activity - to develop and implement innovations and implement marketing complex activities aimed at the commercialization of innovations. The main factors that significantly affect the decision of enterprises to develop and implement innovative projects, as well as those factors that hinder the implementation of innovative activities have been determined. An approach to the formation of an innovative marketing complex is proposed. The approaches and positions to the marketing of innovations at the enterprise are determined, their influence on the efficiency of the enterprise is indicated. Marketing in the management of enterprise development is characterized. A systematic analysis of approaches to determining the role and place of marketing in the innovation sphere has been carried out. The practice of using marketing tools and methods in the domestic enterprises innovation activities is analyzed. The characteristics that determine the specifics of modern innovation marketing tools are determined. A complex of innovative marketing is proposed. The ways of financing innovative activity of Ukrainian enterprises are investigated. The authors refer to the search for partners for innovation activities (suppliers, intermediaries, consumers, financial institutions, etc.) as an important aspect of increasing the effectiveness of innovative marketing. The ways of further development of marketing innovations’ tools and methods and their practical application are outlined.